Two‐Dimensional Metal Halide Perovskites: Theory, Synthesis, and Optoelectronics. Issue 3 (12th January 2017) - Huo, Chengxue; Cai, Bo; Yuan, Zhao; Ma, Biwu; Zeng, Haibo
Abstract : Two‐dimensional (2D) materials attract great attention due to their unique and novel properties in optics, electronics, magnetics, etc. Various 2D materials have been developed since the discovery of graphene, including hexagonal boron nitrides (h‐BNs), transition‐metal dichalcogenides (TMDs), black phosphorus, and so on. Meanwhile, metal halide perovskites are also of great interest because of their high absorbance, high quantum yield, color tunability in the visible‐light range, and high color purity with narrow full width at half maximum (FWHM). Thus, what happens if 2D materials and metal halide perovskites combine? Here work on 2D metal halide perovskites, a class of new 2D materials, is introduced. Besides the advantages of metal halide perovskites, such as high quantum yield, high color purity, and so on, 2D materials are suitable for flexible and wearable devices, giving 2D metal halide perovskites a more and more important role in energy, information displays, illumination, and many other applications. Abstract : 2D metal halide perovskites are metal halide perovskites with a 2D nanostructure. Because of the 2D nanostructure, these perovskites show unique properties based on the quantum confinement effect. Combining the advantages of 2D materials and perovskites, 2D metal halide perovskites have great potential application in optoelectronic devices, such as in solar cells, photodetectors, light‐emitting diodes (LEDs), and optically pumped lasers.